Power Outages and Production Efficiency of Firms in Africa - Abotsi, Anselm Komla (International Journal of Energy Economics and Policy, 2016)
Literature shows that power generation capacity in sub-Sahara Africa is lower than that of any other region in the world and capacity growth has also stagnated. Africa currently faces major electricity shortages with a number of power outages which has the tendency of rendering many firms less efficient in their production. This study therefore seeks to find the impact of power outages on production efficiency of firms in Africa. The source of data is the World Business Environment Survey conducted by the World Bank. The analysis deployed stochastic production frontier and a two-tail Tobit models. The finding shows that the number of power outages experienced in a typical month has a negative impact on the production efficiency of firms in Africa. This call for immense investment projects in new generation capacity in order to ameliorate the negative effect of power crisis on production process of firms in Africa. Keywords: Power Outages, Production Efficiency, Electricity, Africa JEL Classifications: D22, D24, L94